Implementation of Spiritual Education in Improving the Morals of Students at the Tahfizh Mutiara Darul Qur'an Islamic Boarding School, Ngamprah District, West Bandung Regency - Teguh Turwanto; Opik Taupik Kurahman; Lilis Yulistiawati; Tatang Muh Nasir; Rizal Rahmatullah (LP2M STIT Palapa Nusantara, 2023)
The purpose of this writing is to find out the implementation of spiritual education in improving the morals of students at the tahfizh mutiara darul qur'an islamic boarding school, ngamprah district, West Bandung regency. Spiritual education is very appropriate for the achievement of educational goals, especially for the improvement of student learning achievement, but in practice in the field of spiritual education qoetion receives less attention , in fact they only attach importance to logic and methods of general methods that do not contain spiritual elements. This research uses a descriptive method of analysis, namely digging up information that is in accordance with events in the field through the person concerned or respondent. while the approach used in this study is a qualitative approach. Based on the results of the discussion of spiritual education carried out by the Islamic boarding school tahfizh Mutiara Darul Qur'an in this case is very optimal or well implemented, including when new students enter, the students are equipped with an understanding of Islam related to the interaction of men and women by explaining verses of the Qur'an and hadith related to it. An understanding of the necessity of wara' traits in male and female interactions between teenagers is also explained in the briefing. Likewise with the way of dressing, especially the female students. Furthermore, the teachers at the Tahfizh Mutiara Darul Qur'an islamic boarding school are equipped with how to teach in the classroom, including that Spiritual education is applied in all learning materials such as mathematics, science, and others.